Analisis Faktor Keberhasilan Penerapan SISKEUDES dalam Mendukung Terwujudnya Desa Anti Korupsi di Desa Kubang Tangah - Suvenratno; Putri Febri Wialdi (Al-DYAS, 2026)
Transparent, accountable, and effective village financial management is an important aspect of achieving good village governance and preventing corrupt practices. This study aimed to analyze the implementation of the Sistem Keuangan Desa (SISKEUDES) in supporting the realization of Desa Antikorupsi and to identify the factors determining its successful implementation in Kubang Tangah Village, Sawahlunto City. The study employed a qualitative approach. Data were collected through interviews and documentation, while informants were selected purposively based on their involvement in and knowledge of village financial management and SISKEUDES implementation. The data were analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing and verification. Data credibility was assessed through source triangulation. The analysis was based on John F. Rockart’s Critical Success Factors (CSF) perspective, operationalized into six dimensions: leadership support, human resource competence, technological infrastructure, regulations and procedures, coordination and assistance, and community participation. The results showed that SISKEUDES had been successfully implemented in Kubang Tangah Village and supported the processes of village financial planning, implementation, administration, reporting, and accountability. Implementing the system contributed to more orderly, transparent, and accountable financial management, thereby supporting corruption prevention efforts. Its successful implementation was determined by leadership commitment, officials’ competence strengthened through training and experience, generally adequate technological infrastructure, compliance with regulations and procedures, continuous coordination and assistance, and community participation through village deliberations, information disclosure, and oversight. Although internet network and server disruptions still occurred, these constraints were temporary and manageable. These findings confirm that the success of SISKEUDES is determined not only by the application’s technical capabilities but also by the synergy among organizational, human resource, technological, regulatory, assistance, and community participation factors in strengthening village financial governance and supporting the realization of Desa Antikorupsi.